Denmark : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Denmark. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The key findings of Denmark's 2008 Article IV Consultation are examined. The global liquidity crisis put the financial sector under severe stress, but most banks have weathered the crisis well owing to strong initial positions and supportive policies. The crisis accelerated a downturn that had begun in 2007 and tilted the balance of macroeconomic risk toward recession. The macroeconomic policy mix is appropriate, including higher interest rates to support the exchange rate peg and an expansionary budget to add a countercyclical thrust to the strong stabilizing effect of Denmark's automatic stabilizers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet